T-Cell Aging-Associated Phenotypes in Autoimmune Disease - Zhao, Tuantuan V.; Sato, Yuki; Goronzy, Jorg J.; Weyand, Cornelia M. (Frontiers in Aging, 2022)
The aging process causes profound restructuring of the host immune system, typically associated with declining host protection against cancer and infection. In the case of T cells, aging leads to the accumulation of a diverse set of T-cell aging-associated phenotypes (TASP), some of which have been implicated in driving tissue inflammation in autoimmune disease. T cell aging as a risk determinant for autoimmunity is exemplified in two classical autoimmune conditions: rheumatoid arthritis (RA), a disease predominantly affecting postmenopausal women and giant cell arteritis (GCA), an inflammatory vasculopathy exclusively occurring during the 6th-9th decade of life. Pathogenic T-cells in RA emerge as a consequence of premature immune aging. They have shortening and fragility of telomeric DNA ends and instability of mitochondrial DNA. As a result, they produce a distinct profile of metabolites, disproportionally expand their endoplasmic reticulum (ER) membranes and release excess amounts of pro-inflammatory effector cytokines. Characteristically, they are tissue invasive, activate the inflammasome and die a pyroptotic death. Patients with GCA expand pathogenic CD4+ T cells due to aberrant expression of the co-stimulatory receptor NOTCH1 and the failure of the PD-1/PD-L1 immune checkpoint. In addition, GCA patients loose anti-inflammatory Treg cells, promoting tissue-destructive granulomatous vasculitis. In summary, emerging data identify T cell aging as a risk factor for autoimmune disease and directly link TASPs to the breakdown of T cell tolerance and T-cell-induced tissue inflammation.